Pengaruh Budaya Organisasi dan Gaya Kepemimpinan serta Pengembangan Karyawan terhadap Kepuasan Kerja dan Kinerja Karyawan pada Perusahaan Ritel di Sulawesi Selatan - Maryani -; Armanu Thoyib; Margono Setiawan; Ubud Salim (Jurnal Aplikasi Manajemen, 2012)
The research objective are to explain the connection between employee performance and organization culture, leadership style, employee development and job satisfaction with organization culture in order to increase employee performance. The research perform with explanatory research, which done in modern retail company (hypermart) in South Sulawesi. The research sample about 250 respondents of total 2.312 member of employee population, taken by random sampling from each company type and job type of retail company proportionally. Data was analyzed by Structural Equation Model (SEM). The result indicated that organization culture can support a right leadership style election in order to increase job satisfaction and employee performance. A right leadership style in one hand can develop employee, increase job satisfaction and increase employee performance in the other hand. A good growing of employee finally can perform a better employee performance. On the contrary, organization culture which can not develop employee and leadership style which can not perform employee improvement also can not build a job satisfaction.Keywords: employee performance, job satisfaction, employee development, leadership style and organization culture.